Simultaneous and synchronous bilateral endoscopic treatment of urolithiasis: a multicentric study - ŞENER, TARIK EMRE; TANIDIR, YILÖREN (POLISH UROLOGICAL ASSOC, 2019)
Introduction The general prevalence of bilateral urolithiasis has risen to 15% and bilateral non-simultaneous treatment has been reported to have good outcomes. The objective of this study was to evaluate the effectiveness and safety of simultaneous bilateral endoscopic surgery (SBES). Material and methods An international multicenter analysis was performed between May 2015 and December 2017. All patients with bilateral stone disease that underwent SBES were included. Patients were treated under general anesthesia in either the supine or lithotomy position. Demographic, clinical, intraoperative and postoperative data were analyzed. Results A total of 47 patients were included. Mean age was 53.8 years and 70% of the patients were males. The mean American Society of Anesthesiology (ASA) score was 2. The mean diameter of right-and left-sided stones was 29.43 mm (2-83 mm) and 31.15 (4-102 mm), respectively. Staghorn stones were treated in 18 cases (8 right-sided and 10 left-sided), four of them were defined as complete staghorn. The procedures performed were 42 cases of bilateral URS and PCNL and ureteroscopy. Additionally, 5 bilateral flexible ureteroscopy (fURS) cases were described. Intraoperative complications occurred in five patients: four of them were classified as Clavien-Dindo (CD) I and one as CD II. Postoperatively, there were two cases with CD I, 6 with CD II and one CD IIIa. The stone-free status was 70%. Residual stones (30%) were detected only on the side treated for high-volume (complete) staghorn calculi. Conclusions SBES is a feasible, effective and safe procedure. It may potentially avoid repeated anesthetic sessions as needed for staged procedures and reduce the length of patients' hospital stay.
Keywords: bilateral; endoscopy; PCNL; simultaneous; stones; ureteroscopy; RETROGRADE INTRARENAL SURGERY; PERCUTANEOUS NEPHROLITHOTOMY; STONE DISEASE; URETEROSCOPY; EFFICACY; SAFETY